THEORETICAL ISSUES OF HOUSING POLICY IN THE YEARS OF UKRAINE'S INDEPENDENCE: HISTORIOGRAPHIC DISCUSSION - Гудзь, Віктор; Помазан, Дмитро (SWorldJournal, 2025)
The work analyzes a complex of scientific literature on theoretical issues of housing policy in Ukraine. The goal is to investigate the historiographical discourse on some theoretical issues of modern housing policy and, in particular, interpretations of